Academic Stress, Physical Activity, and Menstrual Cycle Regularity Among First-Year Midwifery Students at Health Polytechnic of the Ministry of Health Denpasar - Putu Indah Amelia Kartika; I Komang Lindayani; Ni Luh Putu Sri Erawati; Gusti Ayu Tirtawati; Gusti Ayu Marhaeni (Knowledge Dynamics, 2026)
Background: Academic stress and low physical activity are recognized as factors that may disrupt the hypothalamic–pituitary–ovarian axis, leading to menstrual cycle irregularities among young women. First-year midwifery students are particularly vulnerable because of academic demands and sedentary lifestyles. This study aimed to analyze the relationship between academic stress and physical activity and menstrual cycle regularity among first-year midwifery students at the Health Polytechnic of the Ministry of Health, Denpasar. Methods: This analytical cross-sectional study involved 83 first-year midwifery students selected using total sampling. Academic stress was measured using the Student-life Stress Inventory (SSI), while physical activity was assessed using the International Physical Activity Questionnaire–Short Form (IPAQ-SF). Menstrual cycle regularity was determined through a structured questionnaire. Data were analyzed using the Fisher–Freeman–Halton exact test and multivariate logistic regression. Results: Most respondents experienced moderate to severe academic stress (87.9%), low physical activity (92.8%), and irregular menstrual cycles (78.3%). Academic stress was significantly associated with menstrual cycle regularity (p = 0.003). Physical activity was also significantly associated with menstrual cycle regularity (p = 0.026). Multivariate analysis showed that physical activity was the most dominant factor influencing menstrual cycle regularity (OR = 27.692). Conclusions: Academic stress and physical activity were significantly associated with menstrual cycle regularity among first-year midwifery students. Maintaining adequate physical activity and implementing effective stress management strategies are recommended to improve reproductive health among university students.